2021
DOI: 10.1007/s12144-021-01667-x
|View full text |Cite
|
Sign up to set email alerts
|

Latent profile analysis of COVID-19 fear, depression, anxiety, stress, mindfulness, and resilience

Abstract: The purpose of the current study was to identify latent profiles of COVID-19 fear, depression, anxiety, stress, mindfulness, and resilience among university students. A total of 506 university undergraduate and graduate students from various universities were recruited through online platforms in Turkey. Data were collected utilizing self-report scales and were analyzed utilizing latent profile analysis. Results indicated significant relationships among COVID-19 fear, depression, anxiety, stress, resilience, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
52
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 58 publications
(65 reference statements)
13
52
0
2
Order By: Relevance
“…A cross-sectional study of 3454 vocational college students found that perceived social support was negatively correlated with general anxiety as well (Mai et al, 2021 ). Survey from 506 university students in Turkey also justified the negative relationship between social support and quarantine-related anxiety (Yalcin et al, 2021 ). The empirical study conducted in the lockdown in China observed the negative correlation between social support and trait anxiety, and social support was negatively associated with state anxiety (Ao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study of 3454 vocational college students found that perceived social support was negatively correlated with general anxiety as well (Mai et al, 2021 ). Survey from 506 university students in Turkey also justified the negative relationship between social support and quarantine-related anxiety (Yalcin et al, 2021 ). The empirical study conducted in the lockdown in China observed the negative correlation between social support and trait anxiety, and social support was negatively associated with state anxiety (Ao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Resultados similares se han evidenciado en otro estudio realizado en estudiantes universitarios, donde más del 70% de mujeres tenían niveles altos de miedo, estrés, ansiedad y depresión frente a las medidas de encierro que tomó el gobierno frente a la pandemia de la COVID-19 (Rodríguez-Hidalgo et al, 2020). De igual manera, un estudio realizado en Turquía (en 506 estudiantes de pregrado) asocia al género femenino positivamente con el miedo frente al estrés frente a la COVID-19 (Yalçın et al, 2021). Entonces queda en evidencia que las mujeres son las que más tendencias al miedo presentan, lo que podría influir en la percepción de las repercusiones académicas que tienen.…”
Section: Discussionunclassified
“…Resilience is pivotal to maintaining balance on individual and societal levels and is especially relevant during the Covid-19 pandemic ( 55 ). Covid-19 studies on wellbeing emphasise resilience as mediating the negative outcomes related to Covid-19 stress and fears ( 56 , 57 ). According to the challenge model of resilience ( 58 ), an optimal range of stress exposure exists within which individuals can cultivate resilient response.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate a need to focus on differential effects between student subgroups to address gaps in available knowledge ( 7 , 18 , 57 ). As such, the current study included model fit tests for student subgroups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation